Pemanfaatan Low Resolution Prototipe (LRP) pada Engineering Design Process (EDP) di Jurusan Teknik Elektro Universitas Maritim Raja Ali Haji (UMRAH) - Nusyirwan, Deny (Jurnal Sustainable: Jurnal Hasil Penelitian dan Industri Terapan, 2018)
The aplication of Low Resolution Prototype (LRP) in the Engineering Design Process affects the succesfull of an innovation, therefore, it is really an excellent foundation if the engineering schools of universities provide students with engineering background, to be able to understand the engineering design process in general and benefits of low resolution prototype. This paper will explain the basic concept, understanding and will be given an explanation that emphasizes on the use of low resolution prototype in research or development of an innovation.